PERSEPSI MAHASISWA FBIB UNISBANK TERHADAP KONDUSIFITAS KELAS, PENGGUNAAN ALIH KODE DAN TEKNOLOGI INFORMASI OLEH DOSEN DALAM PROSES PEMBELAJARAN - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2016)
The current study aims at analyzing the perception of the students of FBIBUNISBANKwith respect to class conduciveness, the use of code switching andinformation technology in order to depict the profile of teaching and learning processas the basis of further formulating FBIB (Faculty of Language and CulturalStudies)’s public policies. Therefore, a survey method was employed with theresearch instrument for data collection in the form of questionnaire, developed insoftware application called SurveyMonkey (paid application). The questionnairewas then embedded to a website for the respondents to complete. There were 17respondents for classroom conduciveness and 13 respondents for the use of codeswitching and information technology. Findings showed that FBIB classrooms arerelatively conducive in terms of class atmosphere and infrastructure. The use of codeswitching is encouraged for clarification. Meanwhile IT has been used at moderatelevel to complement the process of teaching and learning. It is thereforerecommended that classroom conduciveness be maintained with a regular check-upfor possible instrument breakdown; code switching be selectively used and teachers’computer literacy be upgraded.